ANALISIS PERENCANAAN SISTEM DISTRIBUSI PADA PT. LAFARGE CEMENT INDONESIA ACEH BESAR - Hibatul Khiram, Wirdah Irawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to know the planning and analyzing the value of the increased supply of distribution based on Trend Projection at PT. Lafarge Cement Indonesia. Supply Chain Management defined a problem to get optimal solutions that have an impact on the cost of the supply chain in the process funneling the goods production and services to customers. The sample in this research was the site of a cement packing (Terminal Packing Plant) at PT. Lafarge Cement Indonesia. The method of this research is carried out by means of direct interviews and obesrvasi as an instrument of research. The technique used is Forecasting as analytical methods and variables to know predictions/distribution supply level forecasting. The results of this research show that the distribution system by planning on doing. Significant effect on the level of PT.LCI supply distribution of cement, and the effectiveness  progression of distribution at PT Lafarge Cement Indonesia reached an average of 98% per year.Keyword: Supply Chain, Distribution, Trend Projection